Safety perception in transportation choices: progress and research lines (2016)
(Eng) The contribution of human factors in traffic accidents has been widely acknowledged in road safety research globally. Although there is sufficient evidence linking the individual behavior with traffic accidents, perceptions are not always included in model specifications to study transportation choices. In the context of transportation choices, this review article makes a significant contribution to understand and model safety perception, identifying issues that have not been addressed sufficiently in the literature, such as measuring indicators, inclusion of objective factors and the link between other latent variables and safety perception. Based on this review it will be possible to formulate novel methodological and econometric approaches to address the inclusion of safety perception into choice models and build a methodological framework for modelling safety perceptions in transportation choices.